Future Communication, Computing, Control and Management Volume 1 - Zhang, Ying.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This volume contains revised and extended research articles written by prominent researchers participating in the ICF4C 2011 conference. 2011 International Conference on Future Communication, Computing, Control and Management (ICF4C 2011) has been held on December 16-17, 2011, Phuket, Thailand. Topics covered include intelligent computing, network management, wireless networks, telecommunication, power engineering, control engineering, Signal and Image Processing, Machine Learning, Control Systems and Applications, The book will offer the states of arts of tremendous advances in Computing, Communication, Control, and Management and also serve as an excellent reference work for researchers and graduate students working on Computing, Communication, Control, and Management Research.
From the content: Research of Dynamic Clustering Time Synchronization Algorithm in Wireless Sensor Networks -- Design of on-demand Time Synchronization algorithm in Wireless Sensor Networks -- Power Load Forecasting Based on The Indicators of Industrialization and Urbanization -- Quantum Bit and Square Well in Quantum Computation -- Physical Realization of Harmonic Oscillator Quantum Computer -- Intrusion Detection Model Based on Set Pair Analysis Theory -- Research on Maximum Wind Energy Capturing of Doubly Fed Induction Wind Generator Based on Fuzzy Control Technology.
Keywords: Engineering; Computer engineering; Microwaves; Telecommunication; Engineering; Communications Engineering, Networks; Microwaves, RF and Optical Engineering; Electrical Engineering